SOCIOPRAGMATIC ANALYSIS OF UZBEK AND ENGLISH DRAMAS - Sherbekova Madinabonu Shavkat kizi (Western European Studies, 2024)
This article examines the socio-pragmatic analysis of Uzbek and English dramas using the example of the work of Hemingway and A. Kakhkhar. Socio-pragmatic analysis is a method of reconstructing the meaning of a statement based on the principles of social pragmatics. The general features of linguistic issues in the field of linguistic relations are examined, the possibilities of a socio-pragmatic approach to the study of linguistic discourse in Uzbek and English literature are analyzed.
Keywords: Socio-pragmatic analysis; work; views; linguistics